Application of GI-TPS Model to Skills Critical Thinking and Self Efficacy - Rusmansyah Rusmansyah; Asranudin Asranudin (Universitas Negeri Makassar, 2017)
This research aims to know the: (1) the difference in critical thinking ability of students (2) difference in the results of learning (cognitive, affective, psychomotor) (3) self efficacy of students (4) student response towards the learning model GI-TPS (Guided Inquiry-Think Pair Share) on the hydrolysis of salt. This research use the pretest-posttest design nonequivalent control group design. A sample of 50 research students, namely class XI IPA 2 and XI IPA 3. Samples taken with purposive sampling technique. Engineering data collection using the test the critical thinking ability, cognitive learning results, observations, and the now. Analytical techniques descriptive analyses using data and analysis inferensial (test, test the normality of its homogeneity, and t-test). The results of this study suggest that (1) there is a difference significant critical thinking abilities (2) there is a difference in learning outcomes (cognitive, affective, psychomotor) a significant (3) students who have self efficacy. (4) the students gave positive response towards the learning model GI-TPS material on the hydrolysis of salt.